Morphometry and Morphology of Acromian Process of Scapula (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The acromian process of scapula is project forward from lateral end of spinous process ofscapula. Coracoacromial ligament is extend between coracoid process and acromian process ,it help information of coracoacromial arch, anatomy of this region is important for better understanding of pathologyregarding subacromial bursa ,impingement syndrome .Materials and Methods: Present study was carried out on 74 dry, adult human scapulae 38 left side and 36right side from teaching collection of anatomy department ,sex of the specimen not known ,Scapular length,width ,acromian process length ,width, thickness ,coracoacromial distance ,acromioglenoid distance wasmeasured with the help of vernier caliper, we also found different shape of acromian process.Results: We observed 74 scapula out of them 38 scapula are of type –I which was 51.35%,13 scapulaof type –II which was 17.57%, 23 scapula of type –III which was 31.08%, we observed mean valueacromian length was 4.50±0.52cm, width of acromian process was 2.10±0.26cm, thickness of acromianprocess was 0.78±0.10cm ,acromicoracoid distance was 3.45±0.53cm, distance between acromianprocess and supraglenoid tubercle was 2.48±0.40cm.Conclusion: These findings suggest that the difference in various parameters related to acromian processhelp in better understanding of anatomy and pathology of coracoacromial arch ,rotator cuff and also helpfulto other clinician.
Keywords: Scapula, Acromian process